Changes in trunks and branches of oiled mangrove trees in selected areas of TINMAR, Nueva Valencia, Guimaras. - Macalalag, Scarlet Erngil V.
On august 11, 2006, the oil tanker M/T Solar I sank off the coast of Southern Guimaras and Negros Occidental, releasing two (2) million liters of Bunker C. This was the largest oil spill recorded to date in the Philippines that affected most of the coastal communities in Southern Guimaras and some parts of Iloilo. This has resulted to the oiling of mangroves within Taklong Island National Reserve, as well as to other sensitive habitats., The present paper reports on the monitoring of the health conditions of five species of mangroves found in TINMAR. these species included Rhizophora stylosa, Rhizophora mucronata, Avicennia marina, Rhizophora apiculata and Sonneratia alba. These are the same species that exhibited mortality during the early phase of the incident. this study aimed to monitor the effects of oil on the health conditions of the selected tree species for a five-month period both in Taklong Islnad and Sitio Bagatnan, starting in August 27 until February 2008 only. Specifically, the number of branches, diameter of lenticels on trunks, length of internodes were monitored. Changes in these parameters would be used as possible indicators of oil-stress resulting from the incident. Results showed that in general, there was a significant increase in lenticel diameter ( x = 6mm, a=0.05), and and internodal length was much shorter ( x = 12 mm, a=0.05) in trees found in oiled sites than in unoiled site. Among the species monitored, Rhizophora stylosa and Rhizophora mucronata showed the greater sensitivity to oil as seen by the changes in the monitored paraneters. There was a marked difference between the growth of mangroves in unoiled control areas vis-a-vis the oil contaminated areas. The two species mentioned have an average of 7.5mm and 5.4mm lenticel diameters on trunks, respectively and there was a shortening of internodes at an average of 4.8mm and 4.5mm, respectively. In conclusion, changes in lenticel diameters and internodal lengths are useful indicators of sub-lethal stress experienced by mangroves exposed to oil for long term monitoring purposes.